Analysis of Adaptive and Participatory Leadership Models Study of Educational Institutional Leadership Models - Eneng Siti Suherni; Achmad Wahyudin; Agus Gunawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Adaptive leadership means leadership that is capable and intelligent in dealing with various situations in a variety of events. And, they are not silent with much thought, but move quickly with various actions, to solve challenges with changes that suit needs. Participative Leadership Style is a leadership style where a leader or leader involves his team members to discuss with each other in finding or making a decision. From the discussion that we have studied with the author, we conclude that adaptive leadership and participative leadership are related to each other, namely in participative leadership, the leader tends to invite people to do a job where the leader must be able to adapt to the people who will do the job so that In other words, the participative leadership style is of course included in the adaptive style. Likewise, the adaptive leadership style is definitely accompanied by a participative leadership style because the leader will be able to adapt to the presence of people who want to participate in doing work to achieve a common goal.